2022
DOI: 10.3390/molecules27175717
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography-Mass Spectrometry (LC-MS) Derivatization-Based Methods for the Determination of Fatty Acids in Biological Samples

Abstract: Fatty acids (FAs) play pleiotropic roles in living organisms, acting as signaling molecules and gene regulators. They are present in plants and foods and may affect human health by food ingestion. As a consequence, analytical methods for their determination in biological fluids, plants and foods have attracted high interest. Undoubtedly, mass spectrometry (MS) has become an indispensable technique for the analysis of FAs. Due to the inherent poor ionization efficiency of FAs, their chemical derivatization prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 91 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…According to previous reports, fatty acids usually exhibit insufficient sensitivity in LC–MS/MS because of their low ionization efficiency [ 27 , 28 ]. Therefore, a derivatization reaction was introduced to overcome such problems in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous reports, fatty acids usually exhibit insufficient sensitivity in LC–MS/MS because of their low ionization efficiency [ 27 , 28 ]. Therefore, a derivatization reaction was introduced to overcome such problems in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acids usually exhibit insufficient sensitivity because of their low ionization efficiency [ 27 ]. Therefore, a derivatization step should be applied to overcome such problems [ 28 ]. The existing algae extraction method is complex, requires multiple steps, and has problems with poor extraction reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…The identification and characterization of BFAs and related lipid components, such as eicosanoids in different matrices are of great interest in product development (Mantzourani & Kokotou, 2022).…”
Section: Identification Of Bioactive Fatty Acidsmentioning
confidence: 99%
“…vatization have been developed to quantify FAs(Mantzourani & Kokotou, 2022) Aveiro et al (2020). characterized the polar lipidome of farmed Emiliania huxleyi RCC1250 (strain AC453) using hydrophobic interaction liquid chromatography (HILIC)-MS, MS/ MS, and FA analysis by GC-MS, to scale up its cultivation (photobioreactors) to industrial levels and reported the occurrence of DHA (17.2%) and SDA (11.0%), in E. huxleyi's lipidome.…”
mentioning
confidence: 99%
“…FAs and FOHs are a group of lipid metabolites that are challenging to analyze and ionize. FAs, which are prevalent in biological fluids and tissues and function as signaling molecules and gene regulators, have been connected to illnesses like cancer, obesity, diabetes, and inflammatory diseases. , Only about 0.01% of the total lipids in mammalian tissues are free fatty alcohols, yet they are linked to a number of devastating hereditary diseases, such as Sjögren–Larsson syndrome, Zellweger syndrome, and infant Refsum disease . Hence, the study of endogenous FAs and FOHs could contribute to our understanding of the physiological functions of these molecules in disease progression.…”
Section: Introductionmentioning
confidence: 99%